Role of seton versus conventional techniques in the management of anorectal fistulas - Akhtar, Mohammad Sadik; Alim, Sheikh Saif; Raza, Mohammad Habib; Ali, Wasif Mohammad (International Surgery Journal, 2020)
Background: This study was conducted to compare the use of different setons with conventional management like fistulotomy and fistulectomy in terms of healing (after 1 and 3 months), recurrence and incontinence. Methods: This was a retrospective non-randomized study conducted at JNMCH, Aligarh from January 2018 to June 2019. Patients included- patients (males and females) of age group 18-70 years, patients giving consent. Patients excluded- fistula secondary to- Crohn’s disease, tuberculosis, malignancy, recurrent fistula, pregnant females, immuno-suppressed patients. Results: After 1 month, 17 out of 24 patients (70.8%) of fistulotomy, 48 out of 68 patients (70.6%) of seton group and 21 out of 32 patients (65.6%) of fistulectomy group had their wounds healed (p=0.8693). After 3 months, 19 out of 24 (79.2%) patients of fistulotomy, 61 out of 68 (89.7%) of seton, and 24 out of 32 patients (75%) with fistulectomy had their wound healed (p=0.1374). Recurrence was observed in 5 out of 24 patients of fistulotomy, 10 out of 68 patients of seton use and 5 out of 32 patients with fistulectomy (p=0.7788). 6 out of 24 patients (25%) had incontinence after fistulotomy, 7 out of 68 (10.3%) of seton group and 8 out of 24 (25%) after fistulectomy (p=0.0944). Healing was higher in patients of non-cutting setons as compared to cutting seton (p=0.0252). After 3 months, no difference was observed (p=0.1245). Recurrence higher in cutting setons as compared to non-cutting setons (p=0.0187). Conclusions: Setons are safe, low-cost, less invasive, precise, and cost-effective option for treating simple and complex fistula-in-ano.